NUTRITION IN PREGNANCY WITH DIABETES MELLITUS - Todorovic, Jovana; Dugalic, Stefan; Macura, Maja; Gutic, Bojana; Milincic, Milos; Bozic, Dragana; Stojiljkovic, Milica; Sbutega Filipović, Olivera; Gojnic, Miroslava (Sanamed, 2022)
The nutritional needs of diabetic pregnancies are different from normal pregnancies. Differences in nutritional recommendations can also be seen between pregnant women who are using and who are not using insulin therapy. In this literature review, recommendations for different meal proportions of carbohydrates, proteins, and fats in the diets of pregnant women with diabetes mellitus are listed. Different meal plans were also addressed in this group of patients. The role of exercise in the management of diabetes in pregnancy is undeniable and different approaches found in the literature are presented.
Keywords: diabetes mellitus; pregnancy; nutrition